2021
DOI: 10.3758/s13423-021-01943-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal crowding is a unique phenomenon reflecting impaired target encoding over large temporal intervals

Abstract: Crowding refers to impaired object identification when presented with other objects, and it is well established that spatial crowding-crowding from adjacent objects-affects many aspects of visual perception and cognition. A similar interference also occurs across time-the identification of a target object is impaired when distracting objects precede and succeed it. When such interference is observed with relatively long interitem intervals it is termed temporal crowding. Thus far, little was known about tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 39 publications
5
33
2
Order By: Relevance
“…This common notion is based on various findings showing that about 100–150 ms following the onset of a centrally presented visual stimulus the participants can say quite a lot about it, like indicating the basic category of a natural scene, determining whether or not it contained an animal, and reporting several large objects incorporated in the scene (e.g., Bacon-Macé et al, 2005; Castelhano & Henderson, 2008; Fei-Fei et al, 2007; Greene & Oliva, 2009; Grill-Spector & Kanwisher, 2005; Thorpe et al, 1996). Our task-relevant stimulus was considerably simpler than an image of a natural scene, yet our results and those of Tkacz-Domb and Yeshurun (2021) indicated that the presence of task-irrelevant items degraded the quality of the target representation even when these items appeared more than 400 ms before/after the target. Thus, an initial volatile visual representation may be generated fast, but our current findings suggest that even with central vision, a robust and stable representation requires considerably longer processing time than the common belief.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This common notion is based on various findings showing that about 100–150 ms following the onset of a centrally presented visual stimulus the participants can say quite a lot about it, like indicating the basic category of a natural scene, determining whether or not it contained an animal, and reporting several large objects incorporated in the scene (e.g., Bacon-Macé et al, 2005; Castelhano & Henderson, 2008; Fei-Fei et al, 2007; Greene & Oliva, 2009; Grill-Spector & Kanwisher, 2005; Thorpe et al, 1996). Our task-relevant stimulus was considerably simpler than an image of a natural scene, yet our results and those of Tkacz-Domb and Yeshurun (2021) indicated that the presence of task-irrelevant items degraded the quality of the target representation even when these items appeared more than 400 ms before/after the target. Thus, an initial volatile visual representation may be generated fast, but our current findings suggest that even with central vision, a robust and stable representation requires considerably longer processing time than the common belief.…”
Section: Discussionmentioning
confidence: 52%
“…Based on Tkacz-Domb and Yeshurun (2021) and taking into consideration that online experiments may involve larger variability, we aimed for a sample size of at least 20 participants. A power test for analysis of variance (ANOVA) conducted with the R pwr package (Champely, 2020) using the effect size from Tkacz-Domb and Yeshurun (2021; Cohen’s f = .58) and an alpha level of .05 confirmed that this sample size ( n = 20) provides .95 power for detecting an effect. In the end, due to the exclusion procedures (details below), the final number of participants that were included in the statistical analysis was 21, 23, 20, and 23 in Experiments 1–4, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncrowding effects are not new [17][18][19][20], but they are ubiquitous: uncrowding does not only occur with vernier stimuli as targets, but also with Gabors [20][21][22][23][24][25][26], letters [27,28], textures [29], complex configurations [30,31], audition [32], and haptics ( [33]). Crowding and uncrowding occur both in foveal and peripheral vision, as well as in time [34,35]. As mentioned, except for psychophysics laboratories, (un)crowding is the standard situation in everyday vision, since elements are rarely encountered in isolation.…”
Section: Failures Of the Physiological Frameworkmentioning
confidence: 99%
“…For the central presentation we chose Experiment 1 from the current study because it is similar to Experiment 3, and unlike Experiment 2, its high contrast stimuli match those of Tackz-Domb andYeshurun (2021). For the peripheral presentation we chose Experiment 2 from Tkacz-Domb andYeshurun (2021) because that experiment included the SOAs of 220ms and 420ms which are closest to the SOAs employed in the current study.…”
mentioning
confidence: 99%